2015
DOI: 10.1002/lno.10248
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and physiochemical responses to a whole-lake experimental increase in dissolved organic carbon in a north-temperate lake

Abstract: Over the last several decades, many lakes globally have increased in dissolved organic carbon (DOC), calling into question how lake functions may respond to increasing DOC. Unfortunately, our basis for making predictions is limited to spatial surveys, modeling, and laboratory experiments, which may not accurately capture important whole-ecosystem processes. In this article, we present data on metabolic and physiochemical responses of a multiyear experimental whole-lake increase in DOC concentration. Unexpected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 63 publications
5
56
0
Order By: Relevance
“…Nutrients increase phytoplankton biomass and result in reduced benthic PP because of shading (Vadeboncoeur et al 2003(Vadeboncoeur et al , 2008. Investigators often assume that energy mobilization shifts from benthic and autotrophic toward pelagic and heterotrophic as increasing allochthonous C reduces light availability (Ask et al 2009, Zwart et al 2015. This assumption has led to the prevalent notion that littoral pri-mary producers are of minor importance in the energy budgets of humic lakes.…”
mentioning
confidence: 99%
“…Nutrients increase phytoplankton biomass and result in reduced benthic PP because of shading (Vadeboncoeur et al 2003(Vadeboncoeur et al , 2008. Investigators often assume that energy mobilization shifts from benthic and autotrophic toward pelagic and heterotrophic as increasing allochthonous C reduces light availability (Ask et al 2009, Zwart et al 2015. This assumption has led to the prevalent notion that littoral pri-mary producers are of minor importance in the energy budgets of humic lakes.…”
mentioning
confidence: 99%
“…For example, we found that we could recreate natural DOC concentrations in sediment pore water. This finding is important because whole-ecosystem experiments have differed from smaller lab-based incubations in estimates of DOC dynamics (Zwart et al, 2016). Our method may therefore bridge contrasting approaches to studying lake sediments, i.e.…”
Section: Discussionmentioning
confidence: 98%
“…We focused on modeling C dynamics in the treatment portion of the lake (East Long Lake; area = 3.2 ha), because the surface inlet to the lake enters that basin and therefore we were able to constrain DOC inputs to that basin well. East Long Lake is a dimictic, mesotrophic (total phosphorus: 15.9 ÎŒg L −1 ; chlorophyll‐a: 7.9 ÎŒg L −1 ) lake with a water residence time of 296 days (Zwart et al, , ). Light is attenuated fairly quickly in the water column of East Long Lake (light extinction coefficient: 2.86 m −1 ) due to the high concentration of DOC (Table ).…”
Section: Methodsmentioning
confidence: 99%
“…Rainfall was measured hourly with a tipping bucket rain gauge (TE525MM‐L; Campbell Scientific, Inc.), whereas the DOC and CO 2 concentrations in rainwater were measured twice over the sampling period; therefore, the average concentrations were used to estimate DOC and CO 2 input with rain (Zwart et al, ). Monthly measurements of groundwater discharge showed that the lake perpetually loses water to the regional aquifer; we used average groundwater discharge values to estimate DOC and CO 2 flux to groundwater.…”
Section: Methodsmentioning
confidence: 99%